In Vivo Pharmacokinetics/Pharmacodynamics of Cefquinome in an Experimental Mouse Model of Staphylococcus Aureus Mastitis following Intramammary Infusion. - Yang Yu; Yu-Feng Zhou; Mei-Ren Chen; Xiao Li; Gui-Lin Qiao; Jian Sun; Xiao-Ping Liao; Ya-Hong Liu (PLoS ONE)
Staphylococcus aureus remains the major cause of morbidity of bovine mastitis worldwide leading to massive economic losses. Cefquinome is a fourth generation cephalosporin, which preserves susceptibility and antibacterial activity against S. aureus. This work aims to study the pharmacokinetic (PK) and pharmacodynamic (PD) modeling following intramammary administration of cefquinome against S. aureus mastitis. The mouse model of S. aureus mastitis was developed for the PK/PD experiments. The plasma PK characteristics after intramammary injection of cefquinome at various single doses of 25, 50, 100, 200, 400 μg per gland (both fourth pairs of glands: L4 and R4) were calculated using one-compartment and first-order absorption model. PD study was investigated based on twenty-one intermittent dosing regimens, of which total daily dose ranged from 25 to 4800 μg per mouse and dosage intervals included 8, 12 or 24 h. The sigmoid Emax model of inhibitory effect was employed for PK/PD modeling. The results of PK/PD integration of cefquinome against S. aureus suggested that the percentage of duration that drug concentration exceeded the minimal inhibitory concentration (%T>MIC) and the ratio of area under time-concentration curve over MIC (AUC/MIC) are important indexes to evaluate the antibacterial activity. The PK/PD parameters of %T>MIC and AUC0-24/MIC were 35.98% and 137.43 h to obtain a 1.8 logCFU/gland reduction of bacterial colony counts in vivo, against S. aureus strains with cefquinome MIC of 0.5μg/ml.